Rancang Bangun Website Desa Bumi Harjo - Firda Nurjanah; Khairil Khairil; Venny Novita Sari (UNIVED Press, 2025)
Bumi Harjo Village still faces challenges in delivering information and administrative services manually, which hinders residents' access to village services. To address this issue, a website is needed to facilitate access to information and improve the efficiency of services digitally. The use of information technology at the village level is a strategic step in achieving transparency and better public services. This study aims to design and build an official website for Bumi Harjo Village as a medium of information and communication between the village government and the community. The website is designed with key features such as village profiles, village news and activities, public services, village institution information, budget transparency, and contact pages. The system development method uses the RAD (Rapid Application Development) approach, which allows the design and implementation process to be carried out iteratively and quickly. The technologies used include HTML, CSS, PHP, and MySQL database. The target users of this system are village residents, village officials, and the general public who need access to information related to village activities and services. Testing was conducted using the blackbox testing method to ensure that all functions run as required. The results of this design show that the website can increase transparency, accelerate information dissemination, and support active community participation in village development.